Persistent differences in recruitment variability among co-occurring North Atlantic groundfish species. (11th October 2022) - Johannesen, Edda; Keith, Dave; Fogarty, Michael J; Shackell, Nancy; Frank, Kenneth T
Abstract: Knowledge of recruitment and its variability in marine fish populations contributes to sustainable fisheries but a full understanding remains elusive. An earlier study showed that haddock ( Melanogrammus aeglefinus ) stocks exhibited consistently higher variability and lower reproductive rates compared to cod ( Gadus morhua ) stocks in the geographic regions where they co-occurred. Thus, cod may have a higher resilience to overexploitation, whereas haddock stocks may be more likely to be rescued by chance strong recruitments events. Since that initial study, the ecosystems and stocks have experienced large structural and functional changes, as well as changes in management practice and ocean warming. Here, we updated the previous earlier analysis with new data and found that despite large changes in the ecosystems explored, the patterns of recruitment variability have persisted. Recruitment variability remains higher in haddock than in cod, and the maximum annual reproduction rate at low spawning stock biomass (SSB) remains higher in cod than in haddock, although the latter difference is now less pronounced. Despite the economic and ecological importance of cod and haddock, and their long history of scientific scrutiny, the persistent difference in their reproductive biology remains unexplained.